Pierre Savorgnan De Brazza, a Life, a Story with the Congo - Zéphirin SAH (Randwick International of Social Science Journal, 2022)
Savorgnan De Brazza figures prominently .This character marked the history of the Congo through his work which can be summed up in three missions carried out on Congolese soil. To remember the latter, the capital of the Congo bears his name: Brazzaville, the city of De Brazza. Besides this, many other places of memory in the Congo bear his name. This study focuses on the life of Pierre Savorgnan De Brazza, his story in particular, the one that links him with the peoples of the Congo. Pierre Savorgnan De Brazza is the first European to have arrived in the current Congolese Cuvette. It was after the Franceville stage in Gabon that De Brazza took the road to the Congo via the Plateaux which he now knows well to reach the Congo River. From this trip, the elders retain the revelation of the name of the Sovereign Teke, King Makoko whose treaty with De Brazza, later allowed the foundation of Brazzaville. This study is about De Brazza a life, a story. This sends us back to the man, his life and his story.